Development of Scramble Based Media IPS Material "Important Events Prior to The Proclamation of Indonesian Independence" Grade VI SD N Bedog - Asnafiyah; Aryati, Nur Indah (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2024)
The active learning process requires mature learning tools from the teacher. Determining the right learning media and methods will have a major impact on the success of teachers and students in achieving learning goals. Therefore, it is important for the teacher to adjust the learning tools according to the students and the material they will teach. There are 3 objectives of this study, namely: (1) to determine the development of scrambling-based flashcard media on IPS material "Important Events Prior to the Proclamation of Indonesian Independence for class VI SD N Bedog, (2) to determine the assessment of the development of scramble-based media on IPS material "Important Events Prior to the Proclamation of Indonesian Independence "Class VI of SD N Bedog according to the validator, and (3) knowing the response of class VI students of SD N Bedog to the development of scrambling-based flashcard media on IPS material "Important Events Prior to the Proclamation of Indonesian Independence".This research is a development research. This study uses the Dick and Carry research method, namely ADDIE, with adaptation of the research steps only up to the third step (ADD). The results showed a percentage score of 84.2% from media experts, 85.5% from material experts, 83.6% from linguists, and 100% from class VI teachers at SD N Bedog. Based on this percentage, the assessment categories of media experts, material experts, and teachers are classified as very suitable for use, while the assessment category for linguists is feasible for use. The results of the response of class VI students at SD N Bedog obtained a percentage of 93.8% (positive response). Based on the research that has been done, it is concluded that the development of scrambling-based flashcard media on IPS material "Important Events Prior to the Proclamation of Indonesian Independence" for class VI SD N Bedog meets the eligibility standards and can become social studies learning media at SD N Bedog.